Analysis of Mathematics Connection Ability in Solving Algebra Problems at VIII Grade Junior High School - Rahman, Irwansyah; Wahyuddin, Wahyuddin; Halim, ST Nurhumairah (Al-Khawarizmi, 2022)
This study aims to determine the mathematics connection ability of VIII Grade students in solving algebraic questions in one of the public junior high schools in Makassar City. This research was qualitative. The research subjects consisted of three students selected based on the results of the basic ability test. Data collection techniques used basic ability tests, mathematics connection skills tests, and interviews. Data analysis techniques were data reduction, data presentation, and conclusion. The results showed that: (1) the mathematics connection ability of subjects with high basic abilities met three indicators of mathematical connection ability, namely connecting mathematical concepts, connecting mathematical concepts with other fields of science, and connecting mathematical concepts with everyday life (2) The subject's mathematics connection ability moderate basic ability met two indicators of mathematics connection ability, namely connecting between mathematical concepts and connecting mathematics concepts with everyday life (3) mathematics connection ability of subjects with the low basic ability only meets one indicator of mathematical connection ability, namely connecting between mathematical concepts.